Roche Pakistan (A) : turning around an organization through cultural transformation - Chatman, Jennifer, (SAGE Knowledge. Cases., 2017)
The Roche Pakistan case study focuses on a country in Roche Global's portfolio which was facing challenges. Farrukh Rehan was hired to turnaround the organization which had missed its revenue targets for three years in a row, had low morale, had not launched a new product in eight years, amongst many other issues. Rehan decided that the culture needed to be fixed first in order to ensure future business results. The (A) case outlines the challenges facing Roche Pakistan when Rehan first arrived and what he did to transform the culture and the (B) case outlines the cultural transformation results, challenges, and future issues. The Roche Pakistan case study provides students with an international case study, featuring Pakistan, a country that although has a unique set of challenges, could be a proxy for organizational cultural transformations in other companies and/or developing markets.